Green Machining: Studying the impact of viscosity of Green Cutting fluid on surface quality in straight turning. (August 2019) - Katna, Rahul; Suhaib, M.; Agrawal, Narayan; Singh, Kanwarjeet; Jain, Swati; Maji, S.
Abstract: Cutting fluids are the category of metalworking fluids which are used in metal machining operation. Application of cutting fluids eases metal removal and enhances the productivity of the industry. Cutting fluids have been used for many decades. Lately the industry is looking toward shifting to using biodegradable cutting fluids. In the last decade many researchers have found that cutting fluids derived from edible oils have a potential to be used in place of the mineral oil based products. However there has not been much reported literature on the surface chemistry of the cutting fluids and how they affect the machining outcomes. In this work experiment was done to study the way in which the viscosity of a non mineral oil based cutting fluid affects the surface roughness of the machining product and the interaction mechanism of cutting fluid with the surface is tried to be deduced from the outcome.